2005
DOI: 10.2337/diabetes.54.5.1477
|View full text |Cite
|
Sign up to set email alerts
|

G(−) Anaerobes–Reactive CD4+ T-Cells Trigger RANKL-Mediated Enhanced Alveolar Bone Loss in Diabetic NOD Mice

Abstract: Diabetic patients experience a higher risk for severe periodontitis; however, the underlying mechanism remains unclear. We investigated the contribution of antibacterial T-cell-mediated immunity to enhanced alveolar bone loss during periodontal infection in nonobese diabetic (NOD) mice by oral inoculation with Actinobacillus actinomycetemcomitans, a G(؊) anaerobe responsible for juvenile and severe periodontitis. The results show that 1) inoculation with A. actinomycetemcomitans in pre-diabetic NOD mice does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
143
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(150 citation statements)
references
References 49 publications
7
143
0
Order By: Relevance
“…Similarly MIP-1␣, the chemokine most enhanced in Akita mice, potently enhances osteoclast formation (51), thus raising the possibility that MIP-1␣ directly enhances alveolar bone loss in Akita mice. The Akita cytokine pattern is also consistent with increased T cell recruitment, and receptor activator NF-B ligand-mediated activation of osteoclast precursors by T cells has been shown to contribute to alveolar bone loss (16).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Similarly MIP-1␣, the chemokine most enhanced in Akita mice, potently enhances osteoclast formation (51), thus raising the possibility that MIP-1␣ directly enhances alveolar bone loss in Akita mice. The Akita cytokine pattern is also consistent with increased T cell recruitment, and receptor activator NF-B ligand-mediated activation of osteoclast precursors by T cells has been shown to contribute to alveolar bone loss (16).…”
Section: Discussionmentioning
confidence: 56%
“…Hyperglycemia plays an important role because both insulin-dependent and non-insulin-dependent diabetes patients are affected, and HbA1c levels inversely correlate with periodontal health (14). Several aspects of diabetic damage to the periodontium have been explored, such as the role of AGE (15), T cell activation (16), and polymorphonuclear neutrophil (PMN)-mediated free radical damage (14). PMN are of particular interest because both acute and chronic PMN deficiency (neutropenia) cause severe oral ulcers and periodontal disease, indicating that PMN are essential in oral mucosal defense (17,18).…”
mentioning
confidence: 99%
“…A number of studies focusing on osteoclastogenesis-related factors have reported elevated levels of RANKL in diabetes-associated periodontal tissues (Mahamed et al 2005, Duarte et al 2007b, Lappin et al 2009). Studies in gingival crevicular fluid demonstrated that RANKL and the RANKL to OPG ratio are higher in poorly controlled diabetic patients with periodontitis compared to well-controlled or non-diabetic subjects with similar periodontal status (Santos et al 2010a, Vieira Ribeiro et al 2011.…”
Section: Hyperglycaemia and Alveolar Bone Homeostasismentioning
confidence: 99%
“…They also showed significantly higher receptor activator of nuclear factor kappaB ligand (RANKL) expression and when treated with osteoprotegerin (OPG), diabetic mice showed a significant reversal of alveolar bone loss, as well as reduced RANKL expression. (78). Mechanisms by which diabetes may impact aspects of the innate immune response associated with periodontal tissue loss such as increased cytokine and superoxide production are discussed below.…”
Section: Periodontal Diseasementioning
confidence: 99%